Comparison of chemoradiotherapy with radiotherapy alone for early-stage extranodal natural killer/T-cell lymphoma, nasal type in elderly patients. Issue 6 (3rd June 2018) - Su, Chang; Nguyen, Kevin A.; Bai, Harrison X.; Balaji, Dhikshitha; Cao, Ya; Karakousis, Giorgos; Zhang, Paul J.; Zhang, Guiying; Xiao, Rong
Abstract: It remains controversial whether concurrent or subsequent chemoradiotherapy (CRT) provides additional survival benefits when compared to radiotherapy (RT) alone in localized extranodal natural killer/T-cell lymphoma (ENKTL), nasal type We identified 248 patients from the US National Cancer Data Base who were diagnosed with localized ENKTL from 2004–2014; 68.9% received CRT and 31.1% received RT alone. Over time, the use of CRT increased, while the use of RT alone decreased ( p < .001). On multivariate analysis, CRT was associated with longer OS than RT alone (HR: 0.504; 95% CI: 0.338–0.751; p < .001), while uninsured status and African–American race were associated with shorter OS. The survival advantages of CRT over RT alone persisted on propensity score matching for the entire cohort ( p = .0014) and in a subgroup analysis of elderly patients ( p < .001). In conclusion, patients who received CRT had significantly longer OS than those who received RT alone. These results also apply to elderly patients.